Qualitative and Quantitative Characterization of Monosaccharide Components of Salvia miltiorrhiza, Liguspyragine Hydrochloride, and Glucose Injection - Fa-huan Ge; Xian-peng Ma; Jin-fang Ma; Chang-qiong Bi; Tian-ling Chen; Xiang-dong Zhang; Xue Xiao (Journal of Analytical Methods in Chemistry)
Salvia miltiorrhiza, liguspyragine hydrochloride, and glucose injection (SLGI) was made of Salvia miltiorrhiza Bge., liguspyragine hydrochloride, glucose, and glycerin. There were many kinds of monosaccharide components in SLGI, which might be from the raw material and Salvia miltiorrhiza Bge. Separation was performed on a Phenomenex Luna C18 analytical column (250 mm × 4.6 mm i.d., 5 μm, AccuStandard Inc., USA) at 30°C. The mobile phase consisted of two solvents: 0.1 mol/L phosphate-buffered saline (pH 6.7) (solvent A) and acetonitrile (solvent B) with gradient elution. The flow rate was maintained at 1.0 mL/min. Five kinds of monosaccharide components, glucose, D-mannose, L-rhamnose monohydrate, galactose, and xylose, were detected by precolumn derivatization HPLC, and their contents were compared with each other. And finally, concentrations of glucose in SLGI were determined and they were higher than the values of marked amount, which showed that one source of glucose might be from Salvia miltiorrhiza Bge. in SLGI. The average concentration of glucose was 5.18 g/100 mL, which was near the average value at 5.25 g/100 mL detected by ultraviolet spectrophotometry and also close to the marked amount (5.00 g/100 mL) on the label.